Expert Knowledge in Latin American History Local, Transnational, and Global Perspectives - Aranha, Patricia (Historamericana, 2022)
This book deals with the role of experts in the modernization efforts of Latin American states in the 19th and 20th centuries. It understands expert knowledge as the application of academic knowledge in non-academic contexts.